TERAPI SEL PUNCA NEURAL PADA PENYANDANG STROKE - Tangkuman, Venki F.; Ngantung, Denny J.; Mawuntu, Arthur (UNIVERSITAS SAM RATULANGI, 2013)
Abstract: Stroke is the second order of deaths for the age group above 60 years and the fifth order for the age group 15-59 years. Although there are many kinds of therapies applied to stroke, none are satisfactory cures. An alternative therapy which is very promising, the neural stem cell therapy, is expected to be able to ameliorate stroke patients better, and therefore, can decrease the morbidity and mortality of stroke cases. There are several kinds of stem cells used in research, inter alia embryonal and adult stem cells. The purpose of this stem cell therapy in neurological disorders is to replace the damaged neural cells or to improve their biological function for enhancing brain function. New neuron cells can be produced from stem cell transplantation. Moreover, the mature brain has the ability, although very limited, toÂ produce new neuron cells as a response to brain damage due to stroke. Keywords: neural stem cells, stroke, transplantation. Â Â Abstrak: Stroke merupakan penyebab kematian urutan kedua pada kelompok usia di atas 60 tahun dan urutan kelima pada kelompok usia 15-59 tahun. Sampai sekarang ini stroke belum dapat disembuhkan dengan baik walaupun telah banyak jenis pengobatan yang digunakan. Salah satu pengobatan alternatif yang mungkin kelak akan mampu memulihkan pasien stroke secara memuaskan serta menurunkan angka morbiditas dan mortalitas kasus stroke di seluruh dunia khususnya Indonesia yaitu terapi sel punca neuronal. Transplantasi sel punca pada gangguan neurologik termasuk stroke yaitu untuk menggantikan atau memperbaiki fungsi biologik dari sel neuron yang rusak agar dapat mempertahankan atau memulihkan fungsi otak. Sel neuron baru dapat dihasilkan dari transplantasi sel punca. Selain itu, otak dewasa akan terpicu untuk membuat sel neuron baru sebagai respon terhadap kerusakan sehingga akan meningkatkan kualitas penyembuhan pasien stroke. Kata kunci: sel punca neuronal, stroke, transplantasi.